Humeral lateral condyle fractures in children: redefining the criteria for displacement. Issue 5 (September 2016) - Bakarman, Khalid A.; Alsiddiky, Abdul Monem M.; Alzain, Kholoud O.; Alkhawashki, Hazem M.; Bin Nasser, Ahmed S.; Alsaleh, Khalid A.; Al-Jassir, Fawzi F.; Zamzam, Mohamed M.
Abstract : The aim of this study is to define paediatric lateral humeral condyle fractures prone to later displacement. The authors reviewed 106 children who were treated surgically for this fracture. There were 74 boys and 32 girls with an age range of 3–10 years. The study included 27 minimally displaced and 79 displaced fractures. The average follow-up was 50 months. Binary logistic regression model indicated that 6–8-year-old children with minimally displaced fractures and who underwent immediate surgery have a better chance for satisfactory results. The authors concluded that routine use of 2 mm displacement for treatment decisions should be changed to avoid delayed surgery.